Physical development from the Western and Islamic perspectives - Abd. Hamid, Siti Rafiah (IIUM PRESS, 2011)
This article focuses on the human developmental aspects both from Western and Islamic Perspectives. The discussion touches lifespan development from inception, the embroyonic and fetal stages.